Enhancing Risk Management Maturity in Regional Development: A Case Study of Bogor Regency - Hidayat, Aldiansyah Iqbal; Silitonga, Mala Sondang (KnE Social Sciences, 2025)
Risk management plays a crucial role in regional development by identifying and mitigating risks that may impact the success of an organization and leveraging opportunities that enable organizational achievement. This research aims to analyze the risk maturity level of risk management in Bogor Regency, Indonesia, utilizing a multidimensional model encompassing Strategy, Planning and Goals, Culture, Standards and Procedures, Processes, Roles and Responsibilities, Compliance, and Crisis Resilience. The methodology employed was a qualitative research method, incorporating data collection through literature review and in-depth interviews with prominent figures in risk management within the regency. The findings reveal that the maturity level of risk management in regional development at Bogor Regency remains at a basic level, scoring between 9-16. This score indicates that while basic risk management functions are implemented in alignment with major external requirements, they are performed on a discontinuous basis and lack a systemic approach. To enhance the risk management maturity level, it is essential to formalize the structure of the risk control unit at both regional apparatus and local government levels, strengthen management commitment, and continuously educate employees about risk management. This research is significant as it highlights the current status and provides actionable recommendations to improve risk management practices, ultimately contributing to more effective and resilient regional development in Bogor Regency.